Analisa Finansial Rencana Pembangunan Jalan Tol Palembang - Indralaya - Yuanda, Yudianto; Haneman, Asrullah (Department of Civil Engineering, Diponegoro University, 2008)
Traffic jam often happens on the road for Palembang-Indralaya route Also number of accidents on the road is very high. Therefore distances in 22 kilometers. This research is aimed to make a financial feasibility study on Palembang-Indralaya toll road. The analysis used is traffic analysis from financial revenue side of the toll revenue. The number of traffic growth is taken from the growth of Gross Regional Domestic Product of the Province of South Sumatera which is currently 6.9% on average. From the result of 2007 survey, it is obtained that the average of daily traffic is currently 19,900 smp/2 directions/day. Then, the traffic analysis and financial From the result of cash flow calculation for Palembang-Indralaya toll road, it is obtained that for the calculation of construction of Alternative I Rigid Pavement, the result is not feasible (pessimistic) for implementation because the IRR is 15.84% and for NPV it is Rp 566,454,000,000.00. BEP will be earned in the 22nd year while BCR = 0.75 < 0. For cash flow with construction of Alternative II with Flexible Pavement, the result is not yet feasible to be implemented because the FIRR is 16.92% and for NPV it is Rp 818,541,000,000.00 and BEP is in the 19th year, BCR = 0.63 < 1. Keywords : LHR, Travel Time, Volume Lalu Lintas, Cash Flow, IRR, NPV, BCR, BEP, ABSTRAK Kemacetan lalu lintas terjadi pada jalan jurusan Palembang-Indralaya juga pada jalan tersebut sangat besar untuk mengimbangnya dan menentukan laju peningkat lalu lintas, maka perlu dibuat jalan tol Palembang-Indralaya sepanjang 22 Km. Tujuan dari penelitian ini untuk melakukan studi kelayakan finansial perencanaan pembangunan jalan tol Palembang-Indralaya analisa yang digunakan adalah analisa lalu lintas dari segi finansial revenue dari pendapatan tol sedangkan angka pertumbuhan lalu lintas diambil dari pertumbuhan Produk Domestik Regional Bruto (PDRB) Propinsi Sumatera Selatan pada saat ini rata-rata 6,9 %. Dari hasil survey tahun 2007 didapat lalu lintas harian rata-rata pada saat ini 19.900 smp/2 arah/hari dilanjutkan dengan analisa lalu lintas dan analisa finansial, Dari hasil perhitungan Cash Flow Jalan Tol Palembang â€“ Indralaya didapat untuk perhitungan konstruksi Alternatif I Pile Slab (Rigid Pavement) hasilnya tidak layak (pesimis) untuk dilaksanakan karena IRR yang didapat adalah:15,84% dan untuk NPV di dapat:Rp. 566.454.000.000 BEP di dapat pada tahun ke 22 sedangkan BCR = 0,75 < 0 untuk Cash Flow dengan konstruksi Alternatif II dengan cerucuk gelam (Flexibel Pavement) hasilnya adalah belum layak untuk dilaksanakan karena IRR yang didapat adalah:16,92% dan NPV adalah Rp. 818.541.000.000 dan BEP tahun ke 19 BCR = 0,63 < 1Kata Kunci : LHR, Travel Time, Volume Lalu Lintas, Cash Flow, IRR, NPV, BCR, BEPPermalink: http://ejournal.undip.ac.id/index.php/mkts/article/view/3693[How to cite: Yuanda, Y. dan Haneman, A. (2008), Analisa Finansial Rencana PembangunanÂ Jalan Tol Palembang - Indralaya, Jurnal Media Komunikasi Teknik Sipil, Tahun 16, Nomor 2, pp. 171-186]